Productivity Dynamic of Rice, Corn, and Soybean in Java, Indonesian - Hendrik Johannes Nadapdap (Jurnal Penelitian Pertanian Terapan, 2017)
This study analyzes productivity, productivity growth variability and variety coefficient of rice, corn, and soybeans on the island of Java. The data used in this research is secondary data in time series obtained from the Central Bureau of Statistics from 1996 to 2015. The research shown that the highest rice production in East Java are 5.5 tons per hectare, the highest maize production in West Java are 4.84 tons per hectare and the highest soybean production in Central Java are 1.47 tons per hectare. The highest productivity growth of rice occurred in Banten, while the highest for corn is in West Java, and the highest for soybean is in Central Java. The highest variability in rice productivity achieved by the province of East Java, while the highest for corn commodity is in West Java, and the highest for soybean is in Central Java. The highest coefficient of rice productivity variation is in Banten, while the highest of corn in West Java and the highest of soybeans in DI. Yogyakarta.Keywords: corn, soybeans, rice, productivity, variability